Expert goalkeepers’ and coaches’ views on anticipation and cue utilisation facing backcourt throws in handball goalkeeping - Huesmann, Kim; Schorer, Jörg; Büsch, Dirk; Witt, Jelto; Loffing, Florian (Frontiers in Sports and Active Living, 2023)
Abstract Handball goalkeepers have to act under severe spatio-temporal pressure in both standardised (e.g. 7m penalty) and non-standardised situations (e.g. backcourt throws) which require them to predict action outcome before ball flight is visible. So far, research on goalkeepers’ cue utilisation for anticipation of an opponent’s action has mainly focused on 7m throw situations whereas little attention has been paid to the latter, more complex and far more frequently occurring backcourt throw situations. To address this gap, we conducted semi-structured interviews with N = 6 expert handball goalkeepers and goalkeeper coaches (all of whom were (former) expert handball goalkeepers) on anticipation and cue utilisation when facing backcourt throws. The interviews were subsequently transcribed, coded and results were inductively as well as deductively categorised by means of a thematic analysis. Results reveal a variety of kinematic and contextual cues relevant for action anticipation become available before the game and before or during the throw. Participants reported to use information from the offence (e.g. thrower’s jump; opposing team’s task distribution) and the defence (e.g. defensive players’ strategies, block position) for anticipation in backcourt throw situations. Additionally, we identified several factors that influence cue availability and utilisation. Our findings provide a thorough basis to (a) guide future research that yields questions on kinematic and contextual cue integration and in-situ cue usage as well as (b) inform the development of training programs to foster goalkeepers’ anticipatory skill.